2004
DOI: 10.1143/jjap.43.6721
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric Properties of Ca3NbGa3Si2O14 Single Crystal

Abstract: Langasite-type single crystal Ca3NbGa3Si2O14 (CNGS) was grown by the Czochralski technique. Dielectric, elastic and piezoelectric constants of CNGS were measured by the resonance-antiresonance method. At room temperature, dielectric constants ε11 T/ε0 and ε33 T/ε0 were 17.8 and 27.9, respectively. Electromechanical coupling coefficients k 12, k 25 and k 26 were also determined as 10.9, 17.3 and 11.9%, respectively. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 18 publications
2
40
0
Order By: Relevance
“…The trigonal unit-cell parameters were calculated using the TEROR program [20], according to the peak values of 2θ in the XRPD pattern, where a= 0.809308685 (±0.0001025) nm, c=0.5047688 (±0.0001732) nm and V= 0.28631 nm 3 which were very close to those in Ref. [19]. Fig.…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…The trigonal unit-cell parameters were calculated using the TEROR program [20], according to the peak values of 2θ in the XRPD pattern, where a= 0.809308685 (±0.0001025) nm, c=0.5047688 (±0.0001732) nm and V= 0.28631 nm 3 which were very close to those in Ref. [19]. Fig.…”
Section: Resultssupporting
confidence: 58%
“…Chai et al reported that disorder causes higher acoustic losses and also non-uniform mechanical properties, and the ordered crystals have the advantages of a lower Ga 2 O 3 content, high acoustic velocity and low acoustic loss [7]. Among this class ordered compounds, CNGS has the lowest melting point (1350°C or so) [19], which is beneficial for Bridgman growth. Thus CNGS crystal is grown by the modified Bridgman method firstly.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Internal one is nearly twice as larger as the clamped one and it means that the dominated contribution comes from the internal lattice, i.e., atomic positions relaxation after imposing a homogenous strain on the lattice. For Sr 3 Reference [25] The piezoelectric coefficients of SGG have been computed by using the alchemical pseudo-potentials technique. The piezoelectric coefficient e 11 calculated from experimental structure is presented in table IV.…”
Section: Quartz Is the Most Important Piezoelectric Crystal Widely Usmentioning
confidence: 99%